Gambaran Proses Assembling Pasien Rawat Inap di Rumah Sakit Umum Dharma Yadnya Denpasar Tahun 2019 : An Overview of The Process of Assembling Inpatients in 2019 at The Dharma Yadnya General Hospital Denpasar - Sudiari, MM, Dr. Ir. Made (Bali Medika Jurnal, 2020)
The assembling process is the assembly of medical record documents by analyzing the completeness of medical record files. The assembling officer must make every effort to maintain the completeness of the medical record files. However, based on the results of interviews with medical record officers, incomplete inpatient medical record files were still found. The purpose of this study was to describe the assembling process of inpatients at Dharma Yadnya Hospital. This type of research is descriptive with a cross sectional approach. The results of this study indicate that the medical record assembling process at the Dharma Yadnya General Hospital is in accordance with the existing SOP and has referred to Permenkes Nomor 269/Menkes/Per/III/2008 regarding the contents of inpatient medical records. It's just that there was a delay in coding due to a lack of officers which led to accumulation of medical record files and finding patient complaints due to the long administration process. We recommend that the hospital management recruit medical record officers in order to avoid complaints from health service users.